2018
DOI: 10.1177/0271678x18795789
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid cells as therapeutic targets in neuroinflammation after stroke: Specific roles of neutrophils and neutrophil–platelet interactions

Abstract: Ischemic brain injury causes a local inflammatory response, involving the activation of resident brain cells such as microglia and the recruitment of infiltrating immune cells. Increasing evidence supports that plasticity of the myeloid cell lineage is determinant for the specific role of these cells on stroke outcome, from initiation and maintenance to resolution of post-ischemic inflammation. The aim of this review is to summarize some of the key characteristics of these cells and the mechanisms for their re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 174 publications
(225 reference statements)
1
77
0
Order By: Relevance
“…55 Proinflammatory cytokines released by necrotic cells induce subsequent neutrophil infiltration to ischemic tissue. 56 We found that inflammatory cytokine mRNA expression of IL-1α, IL-1β, IL-6, IL-10, TNF-α, and TGF-β both in vivo and in vitro, and infiltration of neutrophils in vivo did not change with MRS2578 treatment.…”
Section: Fifth Mrs2578 Treatment Exacerbated the Results Of Mnss Andmentioning
confidence: 71%
See 1 more Smart Citation
“…55 Proinflammatory cytokines released by necrotic cells induce subsequent neutrophil infiltration to ischemic tissue. 56 We found that inflammatory cytokine mRNA expression of IL-1α, IL-1β, IL-6, IL-10, TNF-α, and TGF-β both in vivo and in vitro, and infiltration of neutrophils in vivo did not change with MRS2578 treatment.…”
Section: Fifth Mrs2578 Treatment Exacerbated the Results Of Mnss Andmentioning
confidence: 71%
“…In response to brain injury, microglia promptly acquire properties of reactive species generation, antigen presentation, phagocytosis, and the production of inflammatory mediators including IL‐1, TNF‐α, and IL‐6 . Proinflammatory cytokines released by necrotic cells induce subsequent neutrophil infiltration to ischemic tissue …”
Section: Discussionmentioning
confidence: 99%
“…Ischemic stroke induces massive infiltration of blood-borne immune cells into the brain, which are recruited to the site of injury by a variety of chemokines. 3,[6][7][8][9] Monocytes/macrophages are a subset of these immune cells present in high numbers, [10][11][12][13] but their function in the poststroke brain is not well defined. Macrophages have long been known as professional phagocytes due to their high capacity of engulfment.…”
Section: Introductionmentioning
confidence: 99%
“…19 The release of cytokines, chemokines, cellular adhesion molecules (CAMs), and matrix metalloproteinases (MMPs) by damaged neurons and auxiliary cells, such as microglia, astrocytes, and neutrophils, amplifies the neuroinflammatory cascade during the subacute phase of ischemic stroke and TBI. 4,16,19,20 Upregulation of MMPs, in particular, exacerbates localized inflammatory responses by increasing BBB permeability, thereby permitting peripheral leukocytes to infiltrate the injured brain. 19,20 Additionally, CAMs facilitate leukocyte adherence to cerebral vasculature, allowing further recruitment of cells to the injured area.…”
Section: Acute Inflammation In Stroke and Tbimentioning
confidence: 99%
“…4,16,19,20 Upregulation of MMPs, in particular, exacerbates localized inflammatory responses by increasing BBB permeability, thereby permitting peripheral leukocytes to infiltrate the injured brain. 19,20 Additionally, CAMs facilitate leukocyte adherence to cerebral vasculature, allowing further recruitment of cells to the injured area. Activated microglia and astrocytes prolong inflammation into the chronic phase via continued secretion of cytokines, chemokines, and CAMs, thus attracting more peripheral macrophages and neutrophils through the leaky BBB and other novel deleterious microglial and downstream signaling pathways.…”
Section: Acute Inflammation In Stroke and Tbimentioning
confidence: 99%